Fish Diversity Along the Fresh Water Rapti River Basin of Makawanpur, Central Nepal - Dhakal, Debendra Prasad; Gautam, Raj Kumar; Upreti, Bishwas (International Research Journal of MMC, 2025)
This study was conducted in Rapti River in Makawanpur located between latitudes 27° 21’ 23" N to 27° 47’ 00" N and longitudes 84° 08’ 43"E to 85° 11’ 57" E. It was carried out throughout Bhainse to Lothar, border of Makawanpur and Chitwan with a range of about 40 km. The objective of this study was to discover the fish diversity in Rapti River, Makawanpur and to determine the Shannon-Weiner’s and Margalef’s richness diversity indices. A total of 4 stations were set on the basis of human settlement along Bhainse, Hetauda, Manahari and Lothar. The field work was conducted from January 2025 to August 2025 to cover winter and summer seasons. The fishes were collected by employing local fisherman by using locally prepared fishing gears. A total of 40 fish species were collected belonging to 7 orders, 10 families and 25 genera. The order Cypriniformes was the most dominant, comprising 30 species and accounting for 75% of the total collection. It was followed by Siluriformes with 4 species (10%), Anabantiformes with 3 species (7.5%) and Clupeiformes, Synbranchiformes and Beloniformes, each represented by 1 species (2.5%). The Barilius bendilisis comprises the highest frequency of 20.14% of total catch followed by Garra gotyla 8.14%, Puntius ticto 8% and Schistura beazvani 7.71%. The highest Shannon-Weiner’s index was recorded at Manahari (2.47) and lowest at Bhainse (1.97). The high Margalef’s species richness was recorded at Lothar (4.21) and low at Bhainse (1.85). Manahari has the highest diversity and Lothar has the highest richness. This indicate that Lothar has many species but their distribution is slightly less even than in Manahari where the species richness is high. The present study benefit researchers and locals for the conservation of valuable aquatic fish fauna enhancing biodiversity richness.